Search for optimal design of sectional drills with replaceable many-sided plates at railway rails drilling; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Bakanov A. A. (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа